Bioprinted Hydrogels as Vehicles for the Application of Extracellular Vesicles in Regenerative Medicine - Marta Camacho-Cardenosa; Victoria Pulido-Escribano; Guadalupe Estrella-Guisado; Gabriel Dorado; Aura D. Herrera-Martínez; María Ángeles Gálvez-Moreno; Antonio Casado-Díaz (Gels)
Three-dimensional bioprinting is a new advance in tissue engineering and regenerative medicine. Bioprinting allows manufacturing three-dimensional (3D) structures that mimic tissues or organs. The bioinks used are mainly made of natural or synthetic polymers that must be biocompatible, printable, and biodegradable. These bioinks may incorporate progenitor cells, favoring graft implantation and regeneration of injured tissues. However, the natures of biomaterials, bioprinting processes, a lack of vascularization, and immune responses are factors that limit the viability and functionality of implanted cells and the regeneration of damaged tissues. These limitations can be addressed by incorporating extracellular vesicles (EV) into bioinks. Indeed, EV from progenitor cells may have regenerative capacities, being similar to those of their source cells. Therefore, their combinations with biomaterials can be used in cell-free therapies. Likewise, they can complement the manufacture of bioinks by increasing the viability, differentiation, and regenerative ability of incorporated cells. Thus, the main objective of this review is to show how the use of 3D bioprinting technology can be used for the application of EV in regenerative medicine by incorporating these nanovesicles into hydrogels used as bioinks. To this end, the latest advances derived from in vitro and in vivo studies have been described. Together, these studies show the high therapeutic potential of this strategy in regenerative medicine.